2009
DOI: 10.1002/term.151
|View full text |Cite
|
Sign up to set email alerts
|

Sheep embryonic stem-like cells transplanted in full-thickness cartilage defects

Abstract: Articular cartilage regeneration is limited. Embryonic stem (ES) cell lines provide a source of totipotent cells for regenerating cartilage. Anatomical, biomechanical, physiological and immunological similarities between humans and sheep make this animal an optimal experimental model. This study examines the repair process of articular cartilage in sheep after transplantation of ES-like cells isolated from inner cell masses (ICMs) derived from in vitro-produced (IVP) vitrified embryos. Thirty-five ES-like colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…In the literature, different studies have proposed a cell labelling technique to assess the location and the role of specific cell populations at the defect site, but this seems to be somehow impractical for our repair model, dealing with cartilage fragments embedded in a composite scaffold as a source of cells for the repair. On the other hand, a male source of fragments implanted in a female host could represent a possible solution to that issue, due to the possibility to detect cells carrying the Y gene sequence in the repair tissue by in situ hybridisation, as suggested by recent work of Dattena et al (2009). Indeed, the use of scaffold with allogeneic chondral fragments transplanted to recipients of different gender may constitute an alternative to identify the position of the migrating chondrocytes in the repair tissue and to discriminate this particular cell population from the recipient cells of the surrounding tissue.…”
Section: Discussion With Reviewermentioning
confidence: 99%
“…In the literature, different studies have proposed a cell labelling technique to assess the location and the role of specific cell populations at the defect site, but this seems to be somehow impractical for our repair model, dealing with cartilage fragments embedded in a composite scaffold as a source of cells for the repair. On the other hand, a male source of fragments implanted in a female host could represent a possible solution to that issue, due to the possibility to detect cells carrying the Y gene sequence in the repair tissue by in situ hybridisation, as suggested by recent work of Dattena et al (2009). Indeed, the use of scaffold with allogeneic chondral fragments transplanted to recipients of different gender may constitute an alternative to identify the position of the migrating chondrocytes in the repair tissue and to discriminate this particular cell population from the recipient cells of the surrounding tissue.…”
Section: Discussion With Reviewermentioning
confidence: 99%
“…Previous studies have reported that implantation of ESCs or ESC-derived chondrogenic cells promoted cartilage repair in vivo [4][5][6]. However, it is difficult to obtain autologous ESCs for cell transplantation, and an immunologic barrier prevents in vivo long-term engraftment and function of allogenous ESCs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic stem cells and induced pluripotent stem cells may provide universal, unlimited sources of cells with reparative and regenerative capabilities for cartilage lesions because they have a potential for indefinite undifferentiated proliferation and can be induced towards chondrocyte differentiation 100107. Embryonic stem cells have already been used to enhance the healing of cartilage defects in vivo108110 and to allow for the production of a cartilage matrix capable of integrating with defects in human arthritic joint cartilage 111. However, use of embryonic stem cells remains largely controversial for ethical reasons to do with the harvesting of cells from human embryos, and due to safety issues because their use is associated with immune rejection problems and with the formation of teratomas 112.…”
Section: Alternative Sources Of Progenitor Cellsmentioning
confidence: 99%